Tocotrienols induce endoplasmic reticulum stress and apoptosis in cervical cancer cells. Issue 1 (December 2016) - Comitato, Raffaella; Guantario, Barbara; Leoni, Guido; Nesaretnam, Kalanithi; Ronci, Maria; Canali, Raffaella; Virgili, Fabio
Abstract Background We have previously reported that γ- and δ-tocotrienols (γ- and δ-T3) induce gene expression and apoptosis in human breast cancer cells (MDA-MB-231 and MCF-7). This effect is mediated, at least in part, by a specific binding and activation of the estrogen receptor-β (ERβ). Transcriptomic data obtained within our previous studies, interrogated by different bioinformatic tools, suggested the existence of an alternative pathway, activated by specific T3 forms and leading to apoptosis, also in tumor cells not expressing ER. In order to confirm this hypothesis, we conducted a study in HeLa cells, a line of human cervical cancer cells void of any canonical ER form. Results Cells were synchronized by starvation and treated either with a T3-rich fraction from palm oil (10–20 μg/ml) or with purified α-, γ-, and δ-T3 (5–20 μg/ml). α-tocopherol (TOC) was utilized as a negative control. Apoptosis, accompanied by a significant expression of caspase 8, caspase 10, and caspase 12 was observed at 12 h from treatments. The interrogation of data obtained from transcriptomic platforms (NuGO Affymetrix Human Genechip NuGO_Hs1a520180), further confirmed by RT-PCR, suggested that the administration of γ- and δ-T3 associates with Ca2+ release. Data interrogation were confirmed in living cells; in fact, Ca-dependent signals were observed followed by the expression and activation of IRE-1α and of other molecules involved in the unfolded protein response, the core pathway coping with endoplasmic reticulum stress in eukaryotic cells, finally leading to apoptosis. Conclusions Our study demonstrates that γ- and δ-T3 induce apoptosis also in tumor cells lacking of ERβ by triggering signals originating from endoplasmic reticulum stress. Our observations suggest that tocotrienols could have a significant role in tumor cell physiology and a possible therapeutic potential.